AlmsGiving Behavior of Muslim Communities in Indonesia and Malaysia: A Comparative Study - Azhari, Hifizah Nur; Taat, Muhammad Suhaimi; Anwar, Saiful; Fakhri, Ulumuddin Nurul (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2020)
The study aims to (1) find factors influence funding activities through formal and informal zakah institutions for Indonesian and Malaysian Muslims; (2) find the most significant factors that influence funding activities through formal and informal zakah institutions for Indonesian and Malaysian Muslims; (3) compare the generosity of Indonesian and Malaysian Muslim communities. 564 purposive sampling of Muslim communities in Malaysia and Indonesia participated in this study. Artificial Neural Network (ANN) analysis used as a data analysis tool. Two measurement tools used to examines variables, namely; Questionnaire on planned behavior and Questionnaire of trustworthiness. The result is that the most significant factor influencing charity behavior of Malaysian Muslim society is injunctive norms (42.12%). This is followed by descriptive norms (20.50%) and moral norms (14.49%). Whereas among the Indonesian Muslim community, the most significant factor driving people to give alms is the Injunctive Norm (51.55%). This is followed by past behavior (18.06%) and attitude (13.59%).